Effect of Exercise on Cognitive Ability, Cardiovascular Fitness, and Quality of Life in Post-Stroke Patients: Systematic Review and Meta-Analysis - Maingu, Bertha Sylvester; Murti, Bhisma; Widyaningsih, Vitri (Indonesian Journal of Medicine, 2024)
Background: Following a stroke, cognitive ability, and cardiovascular fitness decline, exerting a substantial influence on physical rehabilitation and overall quality of life. Stroke management encompasses a multidisciplinary approach, with emerging studies highlighting the role of exercise in enhancing cognitive ability and cardiovascular fitness post-stroke. This study aims to analyze the effects of exercise on cognitive ability, cardiovascular fitness, and quality of life in stroke survivors, shedding light on potential therapeutic benefits. Subject and Methods: The PICO Model eligibility criteria were employed to execute the article search including P= post-stroke patients; I= exercises C= standard care, O= cognitive ability OR cardiovascular fitness OR quality of life. The study extracted articles from PubMed and ScienceDirect databases, with keywords "exercises" AND "cognitive ability" OR "cardiovascular fitness" OR "quality of life" AND "post-stroke patients". Inclusion criteria required full-text articles with randomized controlled trial (RCT) designs, focusing on post-stroke patients and evaluating improvements in cognitive ability, cardiovascular fitness, or quality of life. PRISMA diagram and Review Manager 5.4.1 tool were used to analyse the selected articles. Results: 25 studies included in the review had 2,110 participants, across Asia; Australia, Europe, North America, and South America eligible for meta-analysis. The result indicated a positive effect of exercise on cognitive ability (SMD=0.68, CI 95% (0.21 to 1.16); p=0.005); cardiovascular fitness (SMD=0.63, CI 95% (0.17 to 1.08); p=0.007) and quality of life (SMD=0.60, CI 95% (-0.08 to 1.27); p=0.080). Conclusion: Engagement in diverse forms and durations of exercise emerges as a crucial element in post-stroke rehabilitation. This intervention signifies a promising avenue toward enhancing cognitive abilities, and cardiovascular fitness, and potentially elevating quality of life among stroke survivors.